Estudo geométrico de um refletor fresnel linear para produção de energia térmica - Muller, Jair Carlos (Universidade do Vale do Rio dos Sinos, 2016)
This paper presents a geometric study of a linear Fresnel reflector for the production of thermal energy with use of a solar tracker for orientation of mirrors. This work was based on the study of the coordinate system used for the calculation of the slope of the mirrors as function of the sun’s position at a given time. The method considers that the solar direct radiation reaches the center of the mirror, whose slope at each instant allows the reflection of this radiation to the center of the absorber located at a given height from the plane containing the axis of the mirrors. Through the study of slope of mirrors, were analyzed the influences caused by the distance between mirrors, the height of receiver, width of the mirrors and the number of mirrors. With these parameters, it was implemented a simulation in MATLAB which provided power values reflected in the secondary concentrator inlet plane, values of losses by shading, blocking, by defocus and the angular position of each row of mirror. Having these data as base was built a controlled solar tracker by an Arduino micro controller, which allows directing the rows of mirrors with a single engine and coupling shaft. The program in micro controller checks the date and time as initial data, then the geographical coordinates of latitude 29° 45 ' 17.979 "S and longitude 51° 9 ' 1.019" W the local. Thus, it was possible to prove, through images reflected by mirrors on the secondary receiver, that the angular position parameters are correct and that the concentration of sunrays in the absorber secondary hub has adequate accuracy, providing the system reliability for its use.
Keywords: Energia solar térmica; Refletor Fresnel linear; Rastreador solar; Solar energy thermal; Linear Fresnel reflector; Solar tracker; ACCNPQ::Engenharias::Engenharia Mecânica